Serotonin Transporter Availability in Early Stage Parkinson's Disease and Multiple System Atrophy. (3rd February 2014) - Suwijn, S. R.; Berendse, H. W.; Verschuur, C. V. M.; de Bie, R. M. A.; Booij, J.
Abstract : Background . Differentiating Parkinson's disease (PD) from multiple system atrophy (MSA) can be challenging especially early in the course of the disease. Previous studies have shown that midbrain serotonin transporter (SERT) availability in patients with established MSA was significantly lower compared to PD. It is unknown if this is also true for early-stage patients. Methods . 77 early-stage, untreated PD patients were recruited between 1995 and 1998, underwent [ 123 I] β -CIT SPECT imaging, and were followed for at least five years. 16 patients were lost to followup, and in 4 the diagnosis was changed to another atypical parkinsonian syndrome, but not in MSA. In 50 patients, the PD diagnosis was unchanged at followup. In seven patients, the diagnosis was changed to MSA at followup. We retrospectively assessed baseline midbrain SERT availability as well as midbrain SERT-to-striatal dopamine transporter (DAT) ratios. Results . No difference in baseline [ 123 I] β -CIT SERT availability was found. The midbrain SERT-to-striatal DAT ratio for whole striatum was significantly lower in patients with PD compared to MSA (P = 0.049 ). However, when adjusting for the disease duration at imaging this difference is not significant (P = 0.070 ). Conclusion . Midbrain SERT availability is not different between early-stage PD and MSA. Therefore, SERT imaging is not useful to differentiate between early PD and MSA.